2004
DOI: 10.1029/2002gb002017
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the carbon dioxide system in the southern Indian Ocean (20°S–60°S): The impact of a warm anomaly in austral summer 1998

Abstract: The interannual variations of the carbon dioxide system and air‐sea CO2 fluxes are analyzed in the southwestern Indian Ocean from both in situ (Océan Indien Service d'Observations cruises in 1998 and 2000) and simulated oceanic CO2 fugacity dissolved inorganic carbon, total alkalinity, and nutrients. During austral summer of 1998, the ocean was warmer from 20°S to 60°S. In the Subtropical Zone (20°S–37°S), the warming, associated with the subtropical dipole pattern, creates an oceanic CO2 source around 2 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 73 publications
1
45
0
Order By: Relevance
“…In this work, we increased the surface data set by including the surface bottle data (<20 m) collected during CTD stations (conductivity–temperature–depth, Seabird 911 and rosette equipped with 24 Niskin bottles). Except for δ 13 C DIC , instrumental techniques for seawater properties have been previously described (Jabaud‐Jan et al, 2004; Metzl et al, 2006; Metzl, 2009).…”
Section: Data Collectionmentioning
confidence: 99%
“…In this work, we increased the surface data set by including the surface bottle data (<20 m) collected during CTD stations (conductivity–temperature–depth, Seabird 911 and rosette equipped with 24 Niskin bottles). Except for δ 13 C DIC , instrumental techniques for seawater properties have been previously described (Jabaud‐Jan et al, 2004; Metzl et al, 2006; Metzl, 2009).…”
Section: Data Collectionmentioning
confidence: 99%
“…The detection of a long-term trend is difficult as observations tend to be most common in the austral summer and studies have shown that changes in sea surface temperature and net production can cause considerable variability in sea-air fluxes at regional scales during the summer months (Jabaud-Jan et al, 2004;Brévière et al, 2006;Borges et al, 2008;Brix et al, 2012). While a few observational studies attempt to describe the longer-term change of the carbon system, they focus on oceanic pCO 2 rather than changes in sea-air CO 2 fluxes (Inoue and Ishii, 2005;Lenton et al, 2012;Metzl, 2009;Midorikawa et al, 2012;Takahashi et al, 2009) or are station studies that may have local influences (Currie et al, 2009).…”
Section: Longer-term Variabilitymentioning
confidence: 99%
“…Due to the relative scarcity of pCO 2 field data in the Southern Ocean, the inter-annual variability of air-sea CO 2 fluxes has seldom been investigated from a purely observational based approach. The impact of warm anomalies on air-sea CO 2 fluxes in the Southern Ocean has to some extent been investigated using cruise-to-cruise comparisons (Jabaud-Jan et al, 2004;Brévière et al, 2006). These two studies show that warm anomalies lead to significant, but opposing, effects on air-sea CO 2 fluxes in different regions of the high latitude Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%